Web Application Implementation Correctness Tests on the Example of the Electronic Document Circulation System - Gabriel JEKATERYŃCZUK; Paweł KACZMAREK; Zbigniew PIOTROWSKI (Communications of International Proceedings, 2021)
As for the present day, a vast range of web applications with various functions exists on the Internet. The end result of all of them is to make them available to users. To make sure that the web application has no errors, it is important to test it prior to release. Each application can be tested against many types of traits. Today, a vast range of tools and technologies for testing and automating them exists on the market. This article indicates the tools and technologies used in the process of testing all layers on the example of the Electronic Document Circulation System. The Authors of the article presented the advantages and disadvantages of testing the implementation of a web application.
Keywords: Web application; web testing; pros and cons of testing.